Teletext System and Its Application in Vietnamese Language Television Broadcasting - Trần Quang Đức; Trần Thu Hà; Trần Minh Sơn (Journal of Technical Education Science, 2007)
The paper gives readers a short overview on the operation of the Teletext system which is used in conjunction with the analog television system to broadcasting supplemental data together with conventional television programs. More than just a tutorial for the well-known Teletext technology, the work focuses on a possible solution to deploy this enhanced service to broadcasting data written in Vietnamese language. The target is to develop the Vietnamese teletext system at the possibly minimum cost. Exploiting the features and capability of the current Teletext, which is largely hardware-supported at present, a compromised solution is proposed. Its implementation and testing are on progress.